Artificial Intelligence Capital and Employment Prospects - Nick Drydakis (Global Labor Organization (GLO), 2024)
There is limited research assessing how AI knowledge affects employment prospects. The present study defines the term 'AI capital' as a vector of knowledge, skills and capabilities related to AI technologies, which could boost individuals' productivity, employment and earnings. Subsequently, the study reports the outcomes of a genuine correspondence test in England. It was found that university graduates with AI capital, obtained through an AI business module, experienced more invitations for job interviews than graduates without AI capital. Moreover, graduates with AI capital were invited to interviews for jobs that offered higher wages than those without AI capital. Furthermore, it was found that large firms exhibited a preference for job applicants with AI capital, resulting in increased interview invitations and opportunities for higher-paying positions. The outcomes hold for both men and women. The study concludes that AI capital might be rewarded in terms of employment prospects, especially in large firms.
Keywords: E24; I26; O14; 330; Artificial Intelligence; Artificial Intelligence Capital; Employment; Wages; Higher Education; Education